Paradigm of Religious Moderation in Curriculum Design for Islamic Religious Education at State Islamic Senior High School of Bangka Belitung - Suparta Suparta; Wahyudi Wahyudi (Jurnal Madania)
The results of several observations regarding the religious tolerance attitudes of students in Bangka Belitung are pretty worrying, even though some tend to be radical. This research explores the paradigm of religious moderation in the Islamic religious education curriculum at Madrasah Aliyah Negeri Bangka Belitung. This research explores qualitatively the application of religious moderation in the curriculum of Islamic religious education material. Research data was taken from the MAN Pangkal Pinang and MAN 1 Muntok curriculum documents. Researchers also surveyed by distributing questionnaires to 346 students from the two schools. The research results show that the content of religious moderation has been integrated into the Islamic religious education curriculum, both in Jurisprudence, History of Islamic Culture, Al-Qur'an Hadith, and Aqidah Akhlak. However, the tendency towards a radical and robust understanding of Islam is still strong. It is evident from the survey results, namely 55.4% of respondents from MAN Pangkal Pinang and 53% of respondents from MAN 1 Muntok stated that adhering to the Pancasila ideology is more important. Almost half of the students do not agree that Pancasila should be made the state ideology. This phenomenon must receive serious attention from the government so that they comply with the laws and regulations of the Republic of Indonesia.